Peran Promosi dalam Mendorong Keputusan Pembelian pada Toko Beng’s Coffee - Agustina, Cica; Lestari, Nada Wafika; Sari, Nadia Yupita (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Sales promotion has a vital role in attracting consumers' attention and influencing purchasing decisions, especially in the beverage industry such as coffee shops. This study aims to analyze the effectiveness of the promotional strategies implemented by Beng's Coffee in encouraging consumer purchase decisions. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation. The results of the study show that promotional strategies such as discounts on special days, loyalty programs with a stamp system, and product bundling have a positive impact on increasing customer buying interest. Promotion through social media has also proven effective in reaching young consumers. The findings show that appropriately designed promotions not only increase sales volume, but also build consumer loyalty to the brand. In addition, consumers tend to feel that they get added value through the promotional programs that are run. Therefore, it is recommended that Beng's Coffee continue to develop promotional innovations that are relevant to market needs in order to maintain competitiveness and expand market share. This research contributes to understanding the importance of the role of promotion in MSME marketing strategies, especially in the culinary sector.